Rare case of multiple splenic abscesses in enteric fever with contained rupture: Successful conservative management in an immunocompetent young adult (Indian Journal of Case Reports, 2026)
Splenic abscess is a rare but potentially life-threatening complication of enteric fever, particularly in immunocompetent individuals. It occurs in <1% of patients with typhoid or paratyphoid fever and has traditionally been managed surgically due to the risk of rupture and sepsis. We report the case of a 22-year-old immunocompetent male with Salmonella paratyphi A infection complicated by multiple splenic abscesses with radiological evidence of contained rupture, who was successfully managed with intravenous antibiotics alone. The patient remained hemodynamically stable without features of generalized sepsis and showed complete clinical and radiological resolution on conservative therapy. This case highlights the importance of considering splenic abscess as a complication of prolonged enteric fever and demonstrates that non-surgical management can be a safe and effective option in carefully selected, stable patients.